An X-linked agammaglobulinemia (XLA) patient with fever and disturbance of consciousness: infection with Torque teno virus?. (February 2022) - Liu, Hui; Zhao, Jiajia; Yang, Liu; Yang, Chuwei; Liu, Yufei
Highlights: Meningoencephalitis in an adult with XLA caused by a probable Torque teno virus infection. Only TTVs were detected by high-throughput sequencing assay. High-throughput sequencing assay is a promising method for identifying pathogens. Summary: This is the first report of meningoencephalitis in an adult male with X-linked agammaglobulinemia caused by a probable Torque teno virus (TTV) infection. TTV was detected in the cerebrospinal fluid samples of the patient by high-throughput sequencing technology. The patient was treated successfully. Abstract X-linked agammaglobulinemia (XLA) is a rare primary immunodeficiency disease caused by mutations in the Bruton's tyrosine kinase (Btk) gene, characterized by recurrent infections and low or undetectable immunoglobulin levels. The most recommended treatment for XLA is lifelong intravenous immunoglobulin (IVIG) replacement therapy. Without treatment, XLA patients are vulnerable to bacterial and viral infections. Meningoencephalitis is a common complication in patients with XLA. Torque teno viruses (TTVs) are ubiquitous in various tissues of healthy people, while TTV infections have been reported only recently. This case study presents the first reported case on the Chinese mainland of meningoencephalitis in an adult male with XLA, most likely caused by TTV. A 27-year-old male presented with fever and severe disturbance of consciousness. Conventional tests, including blood culture and cerebrospinal fluid (CSF) culture, did not reveal any bacterial infections. The clinical presentation, neuroimaging findings, and results of CSF were suggestive of viral meningoencephalitis. Next, TTV was detected in CSF by high-throughput sequencing (HTS) technology. This case suggests that TTV can have a pathogenic effect on patients with severe immunodeficiency disease, and can produce severe clinical symptoms.